Anti-Infective, Anti-Inflammatory, and Immunomodulatory Properties of Breast Milk Factors for the Protection of Infants in the Pandemic From COVID-19 - Quitadamo, Pasqua Anna; Comegna, Laura; Cristalli, Pierpaolo (Frontiers in Public Health, 2021)
COVID 19 pandemic since the end of 2019 spreads worldwide, counting millions of victims. The viral invasion, the systemic inflammation and consequent organ failure are the gravest features of COVID 19 and they are associated with a high mortality rate. No clinically effective vaccines or specific antiviral drugs are currently available for the prevention and treatment of COVID 19 and there is no pre-existing immunity. So, the search for therapeutic solutions to treat the disease is the highest priority among health care providers, government officials, and pharmaceutical industry. The aim of this study is to evaluate the role of breast milk in the COVID 19 pandemic, analyzing its antiviral, anti-inflammatory and immunoregolatory effects, due to bioactive components, so numerous and important for the protection of infants. The study tried to demonstrate that all the components of human milk are capable of performing functions on all the pathogenic events recognized and described in COVID 19 disease. Those human milk factors are well tolerated and practically free of side effects, so breast milk should become a research topic to discover therapies even in this epidemic. In the first part, the mechanisms of protection and defense of the breast milk elements will be delineated, in the second section it will describe the human milk effects in viral infections and it will be hypothesized how the known mechanisms could act in COVID infection.